Robot e cobot nell'impresa e nella scuola Processi formativi e trasformativi nella workplace innovation - ROBASTO, DANIELA (Processi e Linguaggi dell'Apprendimento, 2022)
The book deals with the transversal theme of hymn-technological development through robots and cobots, the introduction of which crosses now business, scholastic and educational contexts. Starting from an introduction aimed at questioning what is meant from for innovation and what could be the minimum conditions for it we can actually speak of innovative contexts, the volume takes the distances from techno-enthusiastic or techno-critical approaches assumed a priori and suggested manages a departure from a win win perspective at any cost which does not properly reflect on some crucial issues in supporting the innovative processes, including the training of workers (in primis), the legal perspectives, as well as the needs in the terms of new tools to ensure the management of health and safety at work. The volume continues by addressing the potential of collaborative robots in helping people to carry out more or less complex tasks, ibid including learning; therefore, some uses of robotics are presented in educational contexts of school or higher education where robotics could be used as a tool to support people with autism, contrast bullying phenomena, help develop skills transversal and space-time trends, also through the use of the so-called swarm robotics. Despite the difference of languages and specific perspectives that distinguish the different chapters, the volume is oriented to a reader curious and aware that business, school and university can play the their game in synergy, learning to listen to each other and to reflect more frequently-mind about the challenges that unite them.